Identify the relationship between CSR and customer loyalty(Case Study: Bank Mellat) - Mostafa Ghazizadeh; Ahmad Sardari; hamed daneshkhahi; hossein reisi (تحقیقات بازار یابی نوین, 2014)
In recent decades, a new cultural values in result of the attainment of knowledge of interdependent organizations, society and the environment has be realize. People have gradually realized that the organizations action take profit and loss for the community . In other words, society expects to receive a more net profit from organizations and they distribution equitable. The aim of this study was to identify the relationship between corporate social responsibility with customer loyality. The research methodology is descriptive - correlation, research type is applied, execution method was survey and data collected method was field. The study population of the study was customers of Bank Mellat in Tehran. The sample was 384 and the method sampling was cluster. To data collect , Rvjyrvtana Hachy Tara (2011) was used. Descriptive statistics were used to describe the status of the subjects. To determine the significance of hypotheses, Pearson's correlation and stepwise regression was used. And to evaluate the acceptability of the coefficient t-test was used. The research results showed that there was a significant relationship between Corporate Social Responsibility with Customer Loyalty.